The Archipelago of Fernando de Noronha: An Intriguing Malformed Toad Hotspot in South America - Toledo, Luis Felipe; Ribeiro, Ricardo [UNESP] (Springer, 2009)
Malformed anurans raise concern among scientists, because deformities may relate to the recent global crisis among amphibian populations, although declining populations also may be associated with other causes (e.g., diseases, over-exploitation, and land use/land cover change). We examined a sample of toads (Rhinella jimi, Bufonidae) from an introduced population in the Archipelago of Fernando de Noronha, Brazil where malformations of anurans were thought to be high. Our sample of 159 specimens from the site revealed that 44.6% of all specimens had one or more malformations. Incidence of malformed toads on the mainland sites was substantially lower: 10.5% at Itamaraca, and 3.7% at Propria. We describe the malformations observed, including six undescribed types of malformation of anurans, and we pose possible hypotheses to explain this high incidence of malformed toads. In addition to existing hypotheses, we suggest for the first time the hypothesis that lack of predation pressures contributes to numbers of malformed toads. We indicate the need of specific studies to understand the causes of malformations in the R. jimi population of Fernando de Noronha, which is thought to be extreme foci of malformed amphibians in the world. Our results may improve local conservation action plans as this is an alien population that may be affecting endemic fauna, and may affect populations in other parts of the world, because toad species of the genus Rhinella are recognized as exceptional colonizers. More importantly, unknown variables in these toads' environment are evidently affecting toads during development, which should be a concern for all species that inhabit the area, perhaps even humans.
Keywords: environmental conservation; Fernando de Noronha; malformed toads; Rhinella jimi